Analisis Kemampuan Pemecahan Masalah dalam Menyelesaikan Soal HOTS untuk Siswa Kelas XI SMAK ST. Dominikus Tambolaka - Lede, Yulius Keremata; Bili, Nopliana; Making, Samuel Rex M (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine problem-solving abilities in solving HOTS questions for Class XI SMAK ST. Dominikus Tambolaka. The type of research used in this research is qualitative research. In this study, the subjects were 9 class XI SMAK ST. Dominikus Tambolaka and the object of this research is problem-solving skills in solving HOTS questions. The data analysis technique used is data reduction, data presentation, and drawing conclusions or verification. Students who meet the high category are 4 people, medium category are 4 people and low category are 1 person. The percentage of students' overall ability test results that can solve problems based on problem solving indikators according to NCTM is for question number 1 the stage of understanding the problem there is 67%, the indikator of compiling a problemsolving plan is 78%, the indikator of solving problems according to plan is 67% and indikators interpret the result there is 44%. For question number 2 the understanding stage of the problem is 78%, the indikator for compiling a problemsolving plan is 78%, the indikator for solving the problem according to plan is 78% and the indikator for interpreting the results is 22%. Then for question number 3 for the indikator of understanding the problem 67%, the indikator of compiling a problemsolving plan is 100%, the indikator of solving the problem according to plan is 78%, and the indikator interpreting the results is 78%